2016
DOI: 10.1016/j.bjbas.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Serological identification and antimicrobial resistance of Salmonella isolates from broiler carcasses and human stools in Beni-Suef, Egypt

Abstract: A B S T R A C TThe present study was designed in order to estimate the prevalence of Salmonella spp. in broiler carcasses and human stools in Beni-Suef province (Egypt). Also, the serological identification and testing of the antimicrobial resistance/susceptibility of the isolates have been done. The obtained results revealed that the prevalence of Salmonella in broiler meat, skin, and pooled giblets (liver, gizzard, and heart) was 76, 80, and 64%, respectively, while in the case of human stools the percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
5
13
2
Order By: Relevance
“…Forty-five isolates were obtained out of the studied cases with an occurrence of 18%. This prevalence was relatively higher than that obtained by Abed [ 19 ], who recovered 15 isolates of P. aeruginosa with a prevalence of 5% from the pericardial sac of broiler chickens with pericarditis and [ 20 ] who recovered seven isolates of P. aeruginosa with a prevalence of 3.5% from the heart blood of broiler chickens with congestion and pericarditis.…”
Section: Discussioncontrasting
confidence: 56%
“…Forty-five isolates were obtained out of the studied cases with an occurrence of 18%. This prevalence was relatively higher than that obtained by Abed [ 19 ], who recovered 15 isolates of P. aeruginosa with a prevalence of 5% from the pericardial sac of broiler chickens with pericarditis and [ 20 ] who recovered seven isolates of P. aeruginosa with a prevalence of 3.5% from the heart blood of broiler chickens with congestion and pericarditis.…”
Section: Discussioncontrasting
confidence: 56%
“…(2006) who found the incidence of salmonella in the 325 samples was (4.9%) . and agreed with Ziada (2007) (2015) who analyzed Thirty poultry samples for Salmonella and found the prevalence of Salmonella was (16.67%), Hassan et al (2016) who tested 75chicken samples and found the salmonella isolates were 55 isolates and the prevalence was (73.3 %), Yadav, et al (2017) who collected twenty three rectal swabs from 23 Captive Ostrich reared in a park situated in Banskhali, Chittagong and found the prevalence of Salmonella was (78.3%).…”
Section: Discussionsupporting
confidence: 88%
“…In this study one isolate of Salmonella kentuky was sensitive to all antibiotics while the other one was resistant to all antibiotics except (neomycin) was intermediate and this agreed with Ammar et al . (2016) who observed that all Salmonella kentucky sensitive to ciprofloxacin and gentamicin and Hassan et al . (2016) who found Salmonella Kentucky isolates exhibited high rates of resistance against the majority of the used antimicrobials, where 100% (14 of 14) were resistant to ciprofloxacin, ampicillin, nalidixic acid and tetracycline, moreover 85.7% (12 of 14) showed resistance against both of cefotaxime and ceftazidime.…”
Section: Serotypingmentioning
confidence: 97%
“…Most importantly, all of the isolates exhibited multi antibiotic resistance ranging from 3 to 9 with average 0.371 MAR index. Other researchers have also reported high percentages of resistance or multi resistance [1,[14][15][16][17][18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…Salmonellosis is known as a chief foodborne disease in humans, resulting in 16 million cases of typhoid fever, 1.3 billion cases of gastroenteritis and 3 million deaths around the world annually [1] . While numerous potential vehicles of transmission exist, poultry meat is considered one of major sources of this organism [2] .…”
Section: Introductionmentioning
confidence: 99%